Respuesta :

Answer:

see explanation

Step-by-step explanation:

given

g(x) = 3x² - 5 then g(t) = 3t² - 5

Also g(t) = - [tex]\frac{7}{2}[/tex] t, hence

3t² - 5 = - [tex]\frac{7}{2}[/tex] t

multiply both sides by 2 to eliminate the fraction

6t² - 10 = - 7t ( add 7t to both sides )

6t² + 7t - 10 = 0 ← in standard form

(t + 2)(6t - 5) = 0 ← in factored form

Equate each factor to zero and solve for t

t + 2 = 0 ⇒ t = - 2

6t - 5 = 0 ⇒ t = [tex]\frac{5}{6}[/tex]

7/2t. That’s my answer but sorry I didn’t work it out